Meta Analysis: Effect of Mammography Screening on Breast Cancer Mortality - Titisari, Bening Rahimi; Widyaningsih, Vitri; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Breast cancer is the most common cancer experienced by women in developing and developed countries. One of the early detection of breast cancer is mammo